PENINGKATAN RUANG LINGKUP PENJUALAN DAN BRAND KERUPUK ATOM KHAS ANAMBAS - Edy Yulianto Putra; Nevi Ariyu De Utami; Gita Aulia; Yeffy Yeffy; Wikandriya Pradinang; Joy Happy Jones (LPPM Politeknik Pratama, 2022)
Anambas which has local specialties whose ingredients are made from fresh tuna and then processed into atomic crackers as a typical Anambas souvenir. There is limited distribution so that the product is only known in certain areas without being promoted outside the city. The business development is due to a lack of marketing and the appropriate management has not been applied. This activity aims to help introduce the Atomic Cracker brand so that it is known to the wider community and increase sales. The method of implementing this activity uses qualitative methods. With data collection techniques observation, documentation and interviews. The results of this activity are updating the logo and product packaging, as well as creating Instagram social media accounts. The conclusion of this activity is that the use of marketing using digital media is a new hope for MSMEs Atomic Crackers Typical Anambas to expand marketing by utilizing digital media and directly. The advice that can be given is to pay more attention to social media by regularly uploading content to attract the attention of consumers and looking for more gift shops to maximize sales.